Do Market Incentives in the Hospital Industry Affect Subjective Health Perceptions? Evidence from the Italian PPS-DRG Reform - Lorenzo Cappellari; Anna De Paoli; Gilberto Turati (Institute for the Study of Labor (IZA), 2014)
We exploit time variation across Italian Regions in the implementation of a prospective pay systems (PPS) for hospitals based on Diagnosis Related Groups (DRGs) to assess their impact on self-assessed health status and on the use of health care services. We consider a survey of more than 600,000 individuals, over the years 1993-2007, with information on both individuals' perceived health and their access to a number of health services. Results suggest that the introduction of market incentives via a fixed-price payment system does not lead to worst health perceptions. Instead, the reform marked a moderate decrease in hospitalization and day hospital treatments, coupled with a clear decrease in the access to emergency services. Results are robust to a number of sensitivity checks.
Keywords: I11; I18; 330; health reforms; self-assessed health